Current developments in immunotherapy in the treatment of multiple myeloma - Koehler, Martin; Greil, Christine; Hudecek, Michael; Lonial, Sagar; Raje, Noopur; Waesch, Ralph; Engelhardt, Monika (Cancer, 2018)
Multiple myeloma (MM) is the second most common hematologic malignancy and represents approximately 10% of all hematological neoplasms. Standard therapy consists of induction therapy followed by high-dose chemotherapy and autologous stem cell transplantation (ASCT) or, if ASCT cannot be performed, standard doublet, triplet, or quadruplet, novel agent–containing induction treatment until progression. Although MM is still regarded as mostly incurable by current standards, the development of several novel compounds, combination therapies, and immunotherapy approaches has raised great hopes about transforming MM into an indolent, chronic disease and possibly achieving a cure for individual patients. Several new inhibitory and immunological agents have been approved or are under intensive investigation and may lead to new therapeutic options for patients with relapsed/refractory MM, for patients ineligible for ASCT, and for patients after ASCT. Especially in the field of immunotherapy, including monoclonal antibodies, checkpoint inhibition, and chimeric antigen receptor T cells, current advances are rapid and highly promising. This review aims to summarize the newest and most promising immunotherapeutic agents for MM, their clinical efficacy, their adverse event (AE) profiles, and the ways in which these AEs can best be overcome or avoided. Cancer 2018;124:2075-85. © 2018 American Cancer Society.
CRIS-Team Scopus Importer:2023-03-23
Keywords: checkpoint inhibition; chimeric antigen receptor (CAR) T cells; immunotherapy; monoclonal antibodies (mAbs); multiple myeloma